Norteña F2007, new variety of wheat for irrigated fields in the northern region of Mexico and El Bajío - Villaseñor Mir Héctor Eduardo; Huerta Espino, Julio; Solís Moya Ernesto; Espitia Rangel, Eduardo; Ireta Moreno, Javier; Galván Lama Roberto (Revista Mexicana de Ciencias Agrícolas, 2018)
Norteña F2007 was developed by the INIFAP ́s breeding program of wheat in collaboration with CIMMYT. This variety is of spring-growth habit, semi-dwarf with 86 cm high and 130 days to maturity; producing 7%, 8% and 12% more than Tacupeto F2001, Kronstad F2004 and Bárcenas S2002, respectively. On average, it outperformed other control varieties such as Saturno S86, Cortazar S96, Rayón F89 and Tarachi F2000, among others, in the regions of El Bajío and northern Mexico. Norteña F2007 is resistant to moderately susceptible to leaf rust and moderately resistant to stripe rust; its grain protein content is 11.5% to 13% and test weight of 77 kg hL-1 and a gluten force 510*10-4 J, which makes it suitable for making bread in the machine industry and as improved smooth gluten flour. It is recommended for wheat areas of El Bajío and northern Mexico, under regular watering planting and limited irrigation.